Acneform eruptions with use of minoxidil-a case report - Anand Vardhan; C Dinesh M Naidu; Mangesh Bankar; Sagar Sharma; Vinay Raghuvanshi (International Journal of Medical Research and Review, 2016)
A 32 year male patient resident of Andaman and Nicobar Islands presented to the dermatology OPD with the chief complaints of acneform eruptions since 1 month after the use of Minoxidil/Aminexil 5% solution for the treatment of Alopecia which he had since 6 months. Diagnosis of androgenic alopecia was made based on the clinical examination and hence treatment with tablet Finpecia (Finasteride) 1mg once daily and 5% Minoxidil/ Aminexil topical solution 1ml thrice daily local application was advised and patient was asked to come back for follow up after a period of 2 months, but the patient returned after 1 month of treatment with the complaints of comedonic eruptions on forehead.